Marketing analysis of retail banking products to improve customer loyalty of Prime Bank Limited - Chowdhury, Nafis (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.